Type VII secretion system and its effect on group B Streptococcus virulence in isolates obtained from newborns with early onset disease and colonized pregnant women - Schindler, Yulia; Rahav, Galia; Nissan, Israel; Valenci, Gal; Ravins, Miriam; Hanski, Emanuel; Ment, Dana; Tekes-Manova, Dorit; Maor, Yasmin (Frontiers in Cellular and Infection Microbiology, 2023)
GBS may cause a devasting disease in newborns. In early onset disease of the newborn the bacteria are acquired from the colonized mother during delivery. We characterized type VII secretion system (T7SS), exporting small proteins of the WXG100 superfamily, in group B Streptococci (GBS) isolates from pregnant colonized women and newborns with early onset disease (EOD) to better understand T7SS contribution to virulence in these different clinical scenarios. GBS genomes [N=33, 17 EOD isolates (serotype III/ST17) and 16 colonizing isolates (12 serotype VI/ST1, one serotype VI/ST19, one serotype VI/ST6, and two serotype 3/ST19)] were analyzed for presence of T7SS genes and genes encoding WXG100 proteins. Most GBS T7SS loci encoded core component genes: essC, membrane-embedded proteins (essA; essB), modulators of T7SS activity (esaA; esaB; esaC) and effectors: [esxA (SAG1039); esxB (SAG1030)]. Bioinformatic analysis indicated that based on sequence type (ST) the clinical GBS isolates encode at least three distinct subtypes of T7SS machinery. In all ST1 isolates we identified two copies of esxA gene (encoding putative WXG100 proteins), when only 23.5% of the ST17 isolates harbored the esxA gene. Five ST17 isolates encoded two copies of the essC gene. Orphaned WXG100 molecule (SAG0230), distinct from T7SS locus, were found in all tested strains, except in ST17 strains where the locus was found in only 23.5% of the isolates. In ST6 and ST19 isolates most of the structure T7SS genes were missing. Galleria mellonella larvae were used to compare virulence between colonizing, EOD, and mutant EOD isolates. The EOD isolate number 118659 (III/ST17) was used for knocking out the essC gene encoding a membrane-bound ATPase, 3 considered the driver of T7SS. EOD isolates demonstrated enhanced virulence in G. mellonella model compared to colonizing isolates. The 118659ΔessC strain was attenuated in its killing ability, and the larvae were more effective in eradicating 118659ΔessC. To conclude, we demonstrated that T7SS plays a role during infection. Knocking out the essC gene, considered the driver of T7SS, decreased the virulence of ST17 responsible for EOD, causing them to be less virulent comparable to the virulence observed in colonizing isolates.